THE ANALYSIS OF TALENT MANAGEMENT STRATEGY USING ORGANIZATIONAL COMPETENCY APPROACH IN PT PINDAD (PERSERO) BANDUNG CITY - Sukoco, Iwan; Fadillah, Ashar Rijal (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2016)
The biggest challenge of management today is wining talent war. Talent war is a situationwhen the company beat their competitors vying with each other to obtain the best talent in thelabor market. One strategy to win this war talent with talent management is implemented to define,discover, develop, and manage and retain talented employees in an effort to achievestrategic goalsand future business needs. The results showed the company has been able to align talentmanagement strategies with business strategies, creating a 360o assessment, developing a talentmindset, but the generational competence approach has not been done in a structured and tends tobe partial.